# ML Aggarwal Factorisation Exe-4.5 Class 9 ICSE Maths Solutions

ML Aggarwal Factorisation Exe-4.5 Class 9 ICSE Maths Solutions .  Step by step solutions of Factorisation problems as council prescribe guideline. Visit official website CISCE for detail information about ICSE Board Class-9.

## ML Aggarwal Factorisation Exe-4.5 Class 9 ICSE Maths Solutions

 Board ICSE Subject Maths Class 9th Chapter-4 Factorisation Topics Solution of Exe-4.5 Questions Academic Session 2024-2025

### Solution of Exe-4.5 Questions

ML Aggarwal Factorisation Exe-4.5 Class 9 ICSE Maths Solutions

#### Que-1:

Sol:  (i) 8x3 + y3

Above terms can be written as,

(2x)3 + y3

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = 2x, b = y

Then, (2x)3 + y3 = (2x + y) ((2x)2 – (2x × y) + y2)

= (2x + y) (4x2 – 2xy + y2)

##### (ii)  64x3 – 125y3

Above terms can be written as,

(4x)3 – (5y)3

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = 4x, b = 5y

Then, (4x)3 – (5y)3 = (4x – 5y) ((4x)2 + (4x × 5y) + 5y2)

= (4x – 5y) (16x2 + 2oxy + 25y2)

#### Que-2:

Sol:   (i) 64x3 + 1

Above terms can be written as,

(4x)3 + 13

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = 4x, b = 1

Then, (4x)3 + 13 = (4x + 1) ((4x)2 – (4x × 1) + 12)

= (4x + 1) (16x2 – 4x + 1)

##### (ii) 7a3 + 56b3

Take out common in all terms we get,

7(a3 + 8b3)

Above terms can be written as,

7(a3 + (2b)3)

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = a, b = 2b

Then, 7[(a)3 + (2b)3] = 7[(a + 2b) ((a)2 – (a × 2b) + (2b)2)]

= 7(a + 2b) (a2 – 2ab + 4b2)

#### Que-3:

Sol:  (i) (x6/343) + (343/x6)

Above terms can be written as,

(x2/7)3 + (7/x2)3

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = (x2/7), b = (7/x2)

Then, (x2/7)3 + (7/x2)3 = [(x2/7) + (7/x2)] [(x2/7)2 – ((x2/7) × (7/x2)) + (7/x2)2]

= [(x2/7) + (7/x2)] [(x4/49) – 1 + (49/x4)]

##### (ii)8x3 – 1/27y3

Above terms can be written as,

(2x)3 – (1/3y)3

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = 2x, b = (1/3y)

Then, (2x)3 – (1/3y)3 = (2x – (1/3y)) ((2x)2 + (2x × (1/3y)) + (3y)2)

= (2x – (1/3y)) (4x2 + (2x/3y) + 9y2)

#### Que-4:

Sol:  (i) x2 + x5

Take out common in all terms we get,

x2(1 + x3)

x2(13 + x3)

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = 1, b = x

= x2 [(1 + x) (12 – (1 × x) + x2)]

= x2 (1 + x) (1 – x + x2)

##### (ii)32x4 – 500x

Take out common in all terms we get,

4x(8x3 – 125)

Above terms can be written as,

4x((2x)3 – 53)

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = 2x, b = 5

= 4x(2x – 5) ((2x)2 + (2x × 5) + 52)

= 4x(2x – 5) (4x2 + 10x + 25)

#### Que-5:

Sol:  (i) 27x3y3 – 8

Above terms can be written as,

(3xy)3 – 23

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = 3xy, b = 2

= (3xy – 2) ((3xy)2 + (3xy × 2) + 22)

= (3xy – 2) (9x2y2 + 6xy + 4)

##### (ii) 27(x + y)3 + 8(2x – y)3

Above terms can be written as,

33(x + y)3 + 23(2x – y)3

(3(x + y))3 + (2(x – y))3

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = 3(x + y), b = 2(x – y)

= [3(x + y) + 2(2x – y)] [(3(x + y))3 – (3(x + y) × 2(2x – y)) + (2(2x – y))2]

= [3x + 3y + 4x – 2y] [9(x + y)2 – 6(x + y)(2x – y) + 4(2x – y)2]

= (7x – y) [9(x2 + y2 + 2xy) – 6(2x2 – xy + 2xy – y2) + 4(4x2 + y2 – 4xy)]

= (7x – y) [9x2 + 9y2 + 18xy – 12x2 – 6xy – 6y2 + 16x2 + 4y2 – 16xy]

= (7x – y) [13x2 – 4xy + 19y2]

#### Que-6:

Sol: (i) a3 + b3 + a + b

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

[(a + b) (a2 – ab + b2)] + (a + b)

(a + b) (a2 – ab + b2 + 1)

##### (ii) a3 – b3 – a + b

(a3 – b3) – (a – b)

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

[(a – b) (a2 + ab + b2)] – (a – b)

(a – b) (a2 + ab + b2 – 1)

#### Que-7:

Sol:   (i) x3 + x + 2

Above terms can be written as,

x3 + x + 1 + 1

Rearranging the above terms, we get

(x3 + 1) (x + 1)

(x3 + 13) (x + 1)

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

[(x + 1) (x2 – x + 1)] + (x + 1)

(x + 1) (x2 – x + 1 + 1)

(x + 1) (x2 – x + 2)

##### (ii) a3 – a – 120

Above terms can be written as,

a3 – a – 125 + 5

Rearranging the above terms, we get

a3 – 125 – a + 5

(a3 – 125) – (a – 5)

(a3 – 53) – (a – 5)

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

[(a – 5) (a2 + 5a + 52)] – (a – 5)

(a – 5) (a2 + 5a + 25) – (a – 5)

(a – 5) (a2 + 5a + 25 – 1)

(a – 5) (a2 + 5a + 24)

#### Que-8:

Sol:  (i) x3 + 6x2 + 12x + 16

x3 + 6x2 + 12x + 8 + 8

Above terms can be written as,

(x3 + (3 × 2 × x2) + (3 × 22 × x) + 23) + 8

We know that, (a + b)3 = a3 + b3 + 3a2b + 3ab2

Now a = x and b = 2

So, (x + 2)3 + 23

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

(x + 2 + 2) ((x + 2)2 – (2 × (x + 2)) + 22)

(x + 4) (x2 + 4 + 4x – 2x – 4 + 4)

(x + 4) (x2 + 2x + 4)

##### (ii) a3 – 3a2b + 3ab2 – 2b3

Above terms can be written as,

a3 – 3a2b + 3ab2 – b3 – b3

We know that, (a – b)3 = a3 – b3 – 3a2b + 3ab2

So, (a – b)3 + b3

We also know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = a – b, b = b

(a – b – b) ((a – b)2 + (a – b)b + b2)

(a – 2b) (a2 + b2 – 2ab + ab – b2 + b2)

(a – 2b) (a2 + b2 – ab)

#### Que-9:

Sol:  (i) 2a3 + 16b3 – 5a – 10b

Above terms can be written as,

2(a+ 8b3) – 5(a + 2b)

2(a3 + (2b)3) – 5(a + 2b)

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

2[(a + 2b) (a2 – 2ab + 4b2)] – 5(a + 2b)

(a + 2b) (2a2 – 4ab + 8b2 – 5)

##### (ii) a3 – (1/a3) – 2a + 2/a

(a3 – (1/a)3) – 2a + 2/a

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

[(a – 1/a) – (a2 + (a × 1/a) + (1/a)2] – 2(a – 1/a)

(a – 1/a) (a2 + 1 + 1/a2) – 2(a – 1/a)

(a – 1/a) (a2 + 1 + 1/a2 – 2)

(a – 1/a) (a2 + (1/a2) – 1)

#### Que-10:

Sol:   (i) a6 – b6

Above terms can be written as,

(a2)3 – (b2)3

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

So, a = a2, b = b2

(a2 – b2) ((a2)2) + a2b2 + (b2)2)

(a2 – b2) (a4 + a2b2 + b4)

##### (ii) x6 – 1

Above terms can be written as,

(x2)3 – 13

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

So, a = x2, b = 1

(x2 – 1) ((x2)2 + (x2 × 1) + 12)

(x2 – 1) (x4 + x2 + 1)

#### Que-11:

Sol:  (i) 64x6 – 729y6

Above terms can be written as,

(2x)6 – (3y)6

[(2x)2]3 – [(3y)2]3

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

So, a = (2x)2, b = (3y)2

[(2x)2 – (3y)2] [((2x)2)2 + ((2x)2× (3y)2) + ((3y)2)2]

(4x2 – 9y2) [16x4 + (4x2 × 9y2) + (9y2)2]

(4x2 – 9y2) [16x4 + 36x2y2 + 81y4] [(2x)2 – (3y)2] [16x4 + 36x2y2 + 81y4]

(2x + 3y) (2x – 3y) (16x4 + 36x2y2 + 81y4)

##### (ii) x3 – (8/x)

Above terms can be written as,

(1/x) (x3 – 8)

(1/x) [(x)3 – (2)3]

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

So, a = x, b = 2

(1/x) (x – 2) (x2 + 2x + 4)

#### Que-12:

Sol:   (i) 250 (a – b)3 + 2

Take out common in all terms we get,

2(125(a – b)3 + 1)

2[(5(a – b))3 + 13]

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

= 2[(5a – 5b + 1) ((5a – 5b)2 – (5a – 5b)1 + 12)]

= 2(5a – 5b + 1) (25a2 + 25b2 – 50ab – 5a + 5b + 1)

##### (ii) 32a2x3 – 8b2x3 – 4a2y3 + b2y3

Take out common in all terms we get,

8x3(4a2 – b2) – y3(4a2 – b2)

(4a2 – b2) (8x3 – y3)

Above terms can be written as,

((2a)2 – b2) ((2x)– y3)

We know that, a3 – b3 = (a – b) (a2 + ab + b2) and (a2 – b2) = (a + b) (a – b)

(2a + b) (2a – b) [(2x – y) ((2x)2 + 2xy + y2)]

(2a + b) (2a – b) (2x – y) (4x2 + 2xy + y2)

#### Que-13:

Sol:   (i) x9 + y9

Above terms can be written as,

(x3)3 + (y3)3

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

Where, a = x3, b = y3

(x3 + y3) ((x3)2 – x3y3 + (y3)2)

(x3 + y3) (x6 – x3y3 + y6)

Then, (x3 + y3) in the form of (a3 + b3)

(x + y)(x2 – xy + y2) (x6 – x3y3 + y6)

(ii)  X6 – 7x3 – 8

Above terms can be written as,

(x2)3 – 7x3 – x3 + x3 – 8

(x2)3 – 8x3 + x3 – 23

(((x2)3) – (2x)3) + (x3 – 23)

We know that, a3 – b3 = (a – b) (a2 + ab + b2)

(x2 – 2x) ((x2)2 + (x2 × 2x) + (2x)2) + (x – 2) (x2 + 2x + 22)

(x2 – 2x) (x4 + 2x3 + 4x2) + (x – 2) (x2 + 2x + 4)

x(x – 2) x2(x2 + 2x + 4) + (x – 2) (x2 + 2x + 4)

Take out common in all terms we get,

(x – 2) (x2 + 2x + 4) ((x × x2) + 1)

(x – 2) (x2 + 2x + 4) (x3 + 1)

So, above terms are in the form of a3 + b3

Therefore, (x – 2) (x2 + 2x + 4) (x + 1) (x2 – x + 1)

—  : End of ML Aggarwal Factorisation Exe-4.5 Class 9 ICSE Maths Solutions :–